KONSEPSI NEGARA KESEJAHTERAAN PADA KONTEKS PEMBANGUNAN WILAYAH - Irwan Suhermi (universitas teuku umar, 2017)
Abstract: The implementation of regional development in Indonesia can not be separated from the process of adoption from the development theory that developed by west experts in the regional planning. In the era of regional autonomy, regional development plays a very important in the development of Indonesia. By using secondary data, this paper tries to explore the development of the region conducted in Indonesia is associated with the concept of a welfare state. The paper ends with a proposed regional development strategy in the future. Kata kunci: Negara kesejahteraan, pembangunan wilayah